Research on Micro⁃Textured CBN Tools for Turning of Copper⁃Nickel Alloy - Chao ZHANG; Shankuo YUE; Yan HE; Lin FAN; Meiling TANG; Jingting SUN (Liaoning Shiyou Huagong Daxue xuebao)
Three types of micro⁃textures, including broken line grooves, longitudinal grooves and 45° oblique grooves, were constructed on the tool surface and the influence of the tool surface micro⁃texture on the tool cutting performance during copper⁃nickel alloy cutting was deeply studied; by controlling a single⁃variable method, the influence of texture width, texture depth, texture spacing and cutting edge margin on the cutting performance was analyzed, the optimal texture parameter range of the longitudinal groove micro⁃texture was determined, and the optimal texture parameters were determined through orthogonal experiments. The results show that compared with the non⁃textured tool, the longitudinal groove micro⁃textured tool can effectively reduce the main cutting force and cutting temperature; the optimal texture width is 85 µm, the texture spacing is 40 µm, the texture depth is 30 µm, and the cutting edge margin is 40 µm; when the optimal micro⁃textured tool is used to process copper⁃nickel alloy, the average main cutting force is reduced by 23.07%, the average value of the maximum cutting temperature is reduced by 22.46%, and the average equivalent stress is reduced by 19.53%, indicating that the residual stress of the workpiece can be effectively reduced and the cutting performance can be improved.